ONE SYSTEM INTEGRATION PENGEMBANGAN GERBANG PURA (GERAKAN BANGUN POTENSI USAHA RAKYAT) DALAM KERANGKA EKONOMI KERTHI BALI - I Putu Fery Karyada; Kadek Oky Sanjaya; Gde Indra Surya Diputra (JURNAL SEWAKA BHAKTI, 2023)
Empowerment activities is to provide an integrated digital system to support the Gerbang Pura program. Gerbang Pura is a collaborative action to manage people's business potential, which is followed by cultivating community creativity in the optimal, sustainable, and sustainable use of existing potentials and resources, as well as increasing rural communities income so that they can gradually build themselves and their environment independently, based on a business network. The strategic target for this empowerment is the Tejakula District government and community economic groups. At the time of system implementation, Gerbang Pura was integrated with a website-based digital system. The features on the website are in the form of displaying pictures and videos of village products; a production area search map; contacts that are directly integrated with WhatsApp; and also the use of QR codes. The application of the QR code aims to make it easier for visitors to the display house Gerbang Pura to access information about the village's products. With the bar code scanner, data can be read more quickly than with the manual method. The input data is processed more precisely because it has a high degree of accuracy, and the incoming data barcode is more precise. QR code users will be directed to visit the website directly so they can access more information regarding the product to be purchased or visited.